Tert-butyldioxophosphorane as metaphosphate analog - Kolodiazhna, A.O.; Grishkun, E.V.; Gudyma, A.O.; Kolodiazhna, O.O.; Sheiko, S.Yu.; Kolodiazhnyi, O.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
The flash-vacuum thermolysis (FVT) of trimethylsilyl tert-butylhalogenophosphonates is performed in an attempt to generate tert-butyldioxophosphorane. The FVT proceeds with elimination of halogenotrimethylsilane to give unstable tert-butyldioxophosphorane readily transforming into a trimer. Tert-butylhalogenophoshonic acids form rather stable salts with trimethylamine, which eliminate triethytamine hydrohalohenide on the heating to afford a trimer.